2020
DOI: 10.3390/ijerph17207678
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Communication during Remote Follow-Up of Users with Pacemakers in Norway: The NORDLAND Study, a Randomized Trial

Abstract: As effective communication is a key ingredient for the provision of quality healthcare services, this study aimed to explore the communication experiences in the remote monitoring of older adults with a pacemaker. The study was based on a non-masked randomized observational design. The Healthcare Communication Questionnaire and in-depth interviews were conducted for data collection. A total of 49 patients participated in the study. The study findings reveal overall positive communication experiences by pacemak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The general positive experience found in our study in both follow-up groups is confirmed and in line with previous studies that analyzed experiences with telehealth devices in cardiology [ 29 , 30 ] or primary care [ 31 , 32 ], given that for the patients, remote communication with the health professionals was a medium that is flexible, convenient, easy to use, and acceptable for managing their health together. Although this study is the first that explores the experiences of the patients and the communication with health providers in both types of follow-up (TD vs. F-F/D), other studies have shown a high satisfaction with both follow-up modalities [ 18 , 19 , 21 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The general positive experience found in our study in both follow-up groups is confirmed and in line with previous studies that analyzed experiences with telehealth devices in cardiology [ 29 , 30 ] or primary care [ 31 , 32 ], given that for the patients, remote communication with the health professionals was a medium that is flexible, convenient, easy to use, and acceptable for managing their health together. Although this study is the first that explores the experiences of the patients and the communication with health providers in both types of follow-up (TD vs. F-F/D), other studies have shown a high satisfaction with both follow-up modalities [ 18 , 19 , 21 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with other studies in which the analysis of the interaction between health professionals and patients demonstrated significant differences in communication between telemedicine and face-to-face meetings [ 37 ]. However, other studies have not shown differences between the communication of the health professionals and patients in either follow-up modalities (Telemedicine vs. in-person visits) [ 29 , 38 ]. Non-verbal communication is an important aspect of the interactions between health professionals and patients.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports very few studies enquiring patients’ experiences in using the last generation of PM models with remote follow-up, especially relating to the communication in these new clinical environments when there is a severe health issue in a very aged population lacking eHealth literacy skills. These studies have shown how patients with remote follow-up received less information about their diagnosis/afflictions [ 13 ] and similar experiences regarding communication than the patients with hospital follow-up [ 14 ]. Other studies have assessed how PM users contact the clinicians, thus emphasizing that this communication particularly relates to technical concerns on the data transmission as well as the monitoring system [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…From patients' perspective, communicating with clinicians from home is acknowledged as a safe and convenient approach, thus indirectly improving QoL. 19,20 Results revealed that almost a quarter of participants had anxiety (25.3%) and depression (26.0%). A relevant recent study among 250 PPM recipients (median 71 years) showed that 27.2% and 14% experienced high levels of anxiety and depression, respectively.…”
Section: Discussionmentioning
confidence: 99%